PENDAMPINGAN LSM TERHADAP PERMASALAHAN ANAK DAN PEREMPUAN PASCA GEMPA DI DIY - Eny Kusdarini (Jurnal Penelitian Humaniora, 2009)
After the occurrence of the earthquake in DIY there are problems of the child and the woman who needed assistance in his solution. Among the NON-GOVERNMENTAL ORGANISATIONS that carried out counselling in the territory of earthquake casualties was the Samin Foundation and Rifka Annisa with the counselling territory of the Bantul Regency that experienced most serious damage when the earthquake happened. Results of the study showed that there are various problems of the child resulting directly from the earthquake, in example the child sadness, dejected, emotional, Frightened, felt guilty and weak, insomnia, having bad dreams. It also found the problem as indirectly results of the earthquake such the problem of the violence against the child, the health of the child who was ignored by his parents, the children stop schooling and was told to help their parents to get money for the family's economics. The problem of the woman post the earthquake that was found, among them is the violence in the household, many women who were discriminated in the public forums, injustice in gender equality, many groups of the woman who did not yet understand about the gender equality. Assistance methods that were applied adapted from the condition for the local community both the form of assistance and assistance material.